A system for magnetooptical cooling and trapping of Rb atoms - Kowalski, Krzysztof; Dimova-Arnaudova, Emiliya; Fronc, Krzysztof; Gateva, Sanka; Głódź, Małgorzata; Lis, Ludwik; Petrov, Lyubomir; Szonert, Jerzy (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
A system for magnetooptical cooling and trapping of Rb atoms built in our laboratory (at Institute of Physics, Polish Academy of Sciences) is briefly discussed. Emphasis is put on some parts of the apparatus designed and constructed in our lab. An arrangement for experiment control (e.g., data acquisition sequence combined with digital laser frequency tuning) is presented.
Optica Applicata, Vol. 36, 2006, nr 4, s. 559-567
Keywords: optyka; magnetooptical trap; cold Rb atoms; instrumentation